Evaluación clínica comparativa de restauraciones con amalgama versus restauraciones con resina en el sector posterior - Lahoud S., Víctor (2002)
The present study consist in to lo evaluate of performance clinic the restorations with amalgam in comparation with the performance clinic of restorations with resins in the posterior sector, during a time of years two was select 120 premolars and molars with caries oclusals, out side caries with pulp compromise and/o periapicals process. The 120 pieces select divided in two groups; group I: 60 pre- molars with amalgam, Group II: 60 premolars restorations with resins. And evaluate clinic in each restorations: permanency, stable, resistense abrasion and integration marginal. The result shows of the restoration with resin was a exict the 80% ¡n clase I, 60 % in clase II (OD-OM), and 55% in clase II (MOD). The restorations with amalgam was exict of'100% ¡n clase I, clase II (OD-OM) and 95% ¡n clase II (MOD). Was necessary Sustitution 4, the each 20 restorations with resin clase I; 8 of each 20 restorations with resin clase II (OD-OM) and 9 at 20 restorations with resin clase II (MOD) in compara-tion with restorations with amalgams clase I and clase II, was do not necesited of sustitution in the 100% of cases clinics treated. The restorations with resin in cavities small (Clase I) was to much duration significative, in comparative with restorations of resin in cavities extra large (clase II).